PEMBERDAYAAN MASYARAKAT DESA KAFAKBEKA MELALUI PRODUKSI MINYAK KEMIRI HERBAL - Anita Trisia Dimu Lobo; Bernadus H. Lekidela, Danyi Olivianus Sunbanu, Juliance Tampada, Dewi Rusdiana Pandhu, Fernandez Gap (JOURNAL OF COMMUNITY DEDICATION, 2025)
This study discusses the empowerment of the Kafakbeka Village community through the development of herbal candlenut oil production as an effort to improve the villagers’ economic welfare. The purpose of this community service journal is to identify the abundant candlenut resources in Kafakbeka Village, analyze the challenges faced by the community in processing herbal candlenut oil, and formulate sustainable development strategies. The research employed a descriptive qualitative method with data collected through observation, interviews, and documentation. The findings reveal that Kafakbeka Village has significant potential for producing herbal candlenut oil with high economic value and broad market opportunities. However, its utilization is constrained by limited knowledge and processing skills, lack of product innovation, and restricted access to capital and marketing channels. Empowerment efforts can be carried out through capacity building of human resources, strengthening community business groups, applying appropriate technology, product innovation, as well as government and business partner support in improving access to capital and distribution networks. By implementing these strategies, herbal candlenut oil production in Kafakbeka Village has the potential to become a leading commodity that enhances community income and competes in wider markets.